Élaboration collaborative d'un dispositif d’enseignement sur l’aménagement des cours d'eau en géographie et éducation à la durabilité (Suisse) - Anne-Sophie Gavin; Alain Pache; Marianne Milano; Emmanuel Reynard (VertigO)
The educational programme in geography has the potential to train students to think about the complex interdependencies between our societies and the environment and their capacity to act as citizens in spatial planning projects. In that respect, the theme of river planning was chosen to build, in a collaborative way, a teaching device based on the mobilisation of multiple types of knowledge. This paper aims to highlight the geographical and didactic knowledge used and the processes that led to its design. Based on a transdisciplinary approach, interviews were conducted with experts in river planning and in didactics, and work sessions were carried out with teachers in geography. The results showed the emergence of different types of knowledge in geography (academic, experts, vernacular), didactic and pedagogy. The researcher played, during this process, the role of mediator between these knowledges. This led to the construction of an innovative device in geography embedded in an education for sustainable development.